<u><em></em></u>
Answer:
![P(A U B ) = \frac{13}{25}](https://tex.z-dn.net/?f=P%28A%20U%20B%20%29%20%20%3D%20%5Cfrac%7B13%7D%7B25%7D)
Step-by-step explanation:
<u><em>STEP:-1</em></u>
Given that events A and B are independent then
P(A ∩B ) = P(A) P(B)
Given that P(A) = 2/5 and P(B) = 1/5
<u><em>STEP:- 2</em></u>
P(A ∩B ) = P(A) P(B)
![P(A U B) = P(A) +P(B) - P(A n B )](https://tex.z-dn.net/?f=P%28A%20U%20B%29%20%3D%20P%28A%29%20%2BP%28B%29%20-%20P%28A%20n%20B%20%29)
![P(A U B ) = P(A) +P(B) - P(A) P(B)](https://tex.z-dn.net/?f=P%28A%20U%20B%20%29%20%3D%20P%28A%29%20%2BP%28B%29%20-%20P%28A%29%20P%28B%29)
<u><em>Step(iii):-</em></u>
<u><em></em></u>
<u><em></em></u>
<u><em></em></u>
<u><em></em></u>
<u><em></em></u>
<u><em></em></u>
<u><em></em></u>
<u><em></em></u>
<u><em /></u>
<u><em /></u>
Answer:
5a-3b+12c
Step-by-step explanation:
(2a - 3b + 5c) - (-3a - 7c)
Distribute the minus sign
2a -3b +5c +3a +7c
Combine like terms
5a-3b+12c
9514 1404 393
Answer:
D. 7
Step-by-step explanation:
The equation is ...
x = a(y +1)² -3
For the point (x, y) = (4, 0), we have ...
4 = a(0 -1)² -3
7 = a . . . . . . . . . . . . add 3, simplify
The leading coefficient is 7.
Answer:
n=0
Step-by-step explanation:
3n+4+14n=4-32n
3n+14n=-32n
17n=-32
17n+32n=0
49n=0
An example is the number 5i